Abdominal pain - a common presentation with unusual diagnosis: a case report - Yeshaswini. P.S. Reddy; Sriviji Senthil Kumaran; Varun Vanka; Asra Rab; Viren Patel (Greater Baltimore Medical Center, 2020)
Acute abdominal pain is a frequent cause for evaluation in the clinic and emergency room. A number of causes of abdominal pain are diagnosed easily based on the history, physical exam, and some laboratory findings. However, unusual conditions may pose a challenge and require invasive procedures for diagnosis. Rare anomalies such as mobile caecum may present as either typical or atypical acute appendicitis. Endometriosis and pinworm infections can also present as acute appendicitis but are uncommon presentations. To increase the awareness of these uncommon causes of appendicitis, we present a 32 year old female who was previously diagnosed with irritable bowel syndrome later found to have all of the above mentioned rare conditions contributing to abdominal pain. She presented to the emergency room with a one day history of acute right lower quadrant abdominal pain along with nausea and non-bilious vomiting. Physical exam revealed right lower quadrant tenderness to palpation. A computerised tomography of the abdomen and pelvis demonstrated a mobile cecum in the left abdomen. She subsequently underwent a diagnostic laparotomy with cecopexy and appendectomy. Pathology of the appendix showed findings suggestive of endometriosis and intraluminal enterobius vermicularis. She was treated with two doses of pyrantel pamoate for the parasitic infection, and subsequently had resolution of her symptoms.